BSPD guidelines for treatment of IH with propranolol. (1st September 2018) - Solman, L.; Glover, M.; Beattie, P.E.; Buckley, H.; Clark, S.; Gach, J.E.; Giardini, A.; Helbling, I.; Hewitt, R.J.; Laguda, B.; Langan, S.M.; Martinez, A.E.; et al.
Summary: Infantile haemangiomas (IH) are common birthmarks in babies consisting of dilated blood vessels. They are also known as strawberry naevi. Most of them grow for a few months, then gradually shrink spontaneously over a period of months or years. However, in about 15% of cases they can cause serious functional problems when they involve important structures such as the eye, ear, mouth, nose and the peri‐anal area. In addition they can sometimes resolve, but leaving significant disfigurement. In 2008 it was reported that the beta‐blocker drug propranolol, given orally (by mouth), was very effective in causing these birthmarks to shrink rapidly. This paper is designed to provide guidance to doctors on how best to administer propranolol to children with IH. Developing the guidelines involved several stages: an international survey of current practice in eight European countries; a systematic review of the literature; collecting current local guidelines from 19 centres leading to the generation of 70 statements. These 70 statements were then scrutinised by 19 experts from relevant specialities (Dermatology, Paediatrics, Paediatric Cardiology and Paediatric ENT surgery). Using an established research protocol, agreement was reached by these experts on 47 statements covering eight categories. These categories include: indications for starting propranolol (i.e. it which situations it should be used); contraindications (i.e. in which situations it should not be used); pre‐treatment tests needed; initiation of treatment; monitoring during treatment and when to stop treatment. They also cover treatment of children with additional medical complications.Although these guidelines are UK‐based, the authors hope that they will be useful in other European countries also.